Catalyst for catalyzing conversion of glucose into 5-hydroxymethylfurfural and preparation method thereof

By synthesizing the mesoporous carbon microsphere catalyst supported by tin, the problems of more side reactions and low selectivity during the conversion of glucose to HMF are solved, and efficient catalytic conversion of glucose to HMF is achieved, which significantly improves the catalytic efficiency.

CN119500101APending Publication Date: 2025-02-25SHANDONG UNIV OF SCI & TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411488076.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

There are many side reactions during the conversion of glucose to 5-hydroxymethylfurfural (HMF), and the selectivity of HMF is low, which affects the catalytic efficiency.

Method used

A preparation method is used to synthesize the mesoporous carbon microsphere catalyst supported by the hard template method, and the catalyst is prepared by impregnating with tin tetrachloride pentahydrate solution by impregnating the catalyst to catalyze the conversion of glucose to HMF.

Benefits of technology

This catalyst has a large specific surface area, excellent pore structure and good hydrothermal stability. It can efficiently catalyze the conversion of glucose into HMF, significantly improving the selectivity of HMF, and providing a green and feasible way for biomass conversion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500101A_ABST
    Figure CN119500101A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy, and particularly discloses a catalyst for catalyzing conversion of glucose into 5-hydroxymethylfurfural and a preparation method of the catalyst. The method is used for solving the problem of low HMF selectivity in the process of converting glucose into HMF. The preparation method comprises the following steps: firstly, synthesizing hollow mesoporous silicon spheres in the presence of absolute ethyl alcohol by taking hexadecyl trimethyl ammonium bromide as a structure-directing agent, ammonia water for providing an alkaline environment and tetraethyl orthosilicate as a silicon source of silicon dioxide; then, filling sucrose serving as a carbon source into the hollow meso-porous silicon spheres, and carbonizing and removing silicon to obtain meso-porous carbon microspheres; and finally, dipping the mesoporous carbon microspheres in a tin tetrachloride pentahydrate solution to prepare the tin-loaded mesoporous carbon microsphere catalyst. The catalyst has a large specific surface area, an excellent pore structure and good hydrothermal stability, has two acidic sites of Lewis acid and # imgabs0 # acid at the same time, and can efficiently catalyze conversion of glucose into HMF.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy, and in particular relates to a catalyst for catalyzing the conversion of glucose into 5-hydroxymethylfurfural and a preparation method thereof. Background Art

[0002] Glucose is the most abundant monosaccharide in the world, so it is very commercially valuable to use it as a starting material for the production of 5-hydroxymethylfurfural (HMF). The biggest challenge nowadays is the side reactions that occur during the conversion of glucose to HMF, such as the condensation of hexose and HMF to produce insoluble humins and soluble polymers, and HMF has low stability and is easily rehydrated to form formic acid and levulinic acid, all of which will lead to reduced selectivity of HMF. Therefore, the choice of catalyst is extremely important. Summary of the invention

[0003] One object of the present invention is to provide a method for preparing a catalyst for catalyzing the conversion of glucose into 5-hydroxymethylfurfural, so as to effectively solve the problem of low selectivity of HMF in the process of converting glucose into HMF.

[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a catalyst for catalyzing the conversion of glucose into 5-hydroxymethylfurfural, comprising the following steps.

[0005] S1. Take hexadecyltrimethylammonium bromide, 25%-28% ammonia water, anhydrous ethanol and distilled water and add them into a beaker in sequence. Heat and stir until the mixture cools to room temperature. Then add tetraethyl orthosilicate and stir vigorously. Let the mixture stand at room temperature for 24 hours and calcine in a muffle furnace to synthesize hollow mesoporous silica spheres.

[0006] S2. The hollow mesoporous silica spheres are dissolved in a sucrose aqueous solution containing sulfuric acid, and baked in an oven twice to obtain a primary filling sample.

[0007] S3. The first filling sample is dissolved in a sucrose aqueous solution containing sulfuric acid, and is baked twice in an oven to obtain a second filling sample.

[0008] The secondary filling sample was calcined in a tubular furnace, then soaked in hydrofluoric acid, and finally washed with deionized water to neutrality to obtain mesoporous carbon microspheres.

[0009] S4. Take tin tetrachloride pentahydrate and dissolve it in deionized water, add mesoporous carbon microspheres and stir, after impregnation treatment, dry in an oven, and finally calcine in a tubular furnace to obtain xSnO2 / MCMs catalyst.

[0010] Furthermore, in step S1, the mass ratio of hexadecyltrimethylammonium bromide to tetraethyl orthosilicate is 1:5.7, the volume ratio of ammonia water, anhydrous ethanol and distilled water is 1:3.74:8.28, and the dosage ratio of hexadecyltrimethylammonium bromide to ammonia water is 1 g:37 mL.

[0011] Furthermore, in step S1, the heating and stirring temperature is 40° C., and the stirring time is 1 hour.

[0012] Furthermore, in step S1, the temperature of the muffle furnace calcination is 550° C., and the calcination time is 6 hours.

[0013] Furthermore, the preparation method of the sucrose aqueous solution containing sulfuric acid in step S2 is: sucrose, 98% concentrated sulfuric acid and deionized water are evenly mixed, and the dosage ratio of the sucrose, concentrated sulfuric acid and deionized water is 12.5g:1mL:50g.

[0014] The preparation method of the sucrose aqueous solution containing sulfuric acid in step S3 is: sucrose, 98% concentrated sulfuric acid and deionized water are mixed evenly, and the usage ratio of the sucrose, concentrated sulfuric acid and deionized water is 16g:1mL:100g.

[0015] Furthermore, in step S2, the oven is baked twice at 100°C for 6 hours and at 160°C for 6 hours respectively; in step S3, the oven is baked twice at 100°C for 6 hours and at 160°C for 6 hours respectively.

[0016] Furthermore, in step S3, the calcination treatment conditions in the tubular furnace are: calcination at 900° C. for 4 hours; in step S3, the mass percentage concentration of hydrofluoric acid is 40%, and the immersion time is 5 hours.

[0017] Furthermore, in step S4, the stirring time is 1 hour, the impregnation treatment time is 6 hours, the oven drying temperature is 60° C., the tubular furnace calcination temperature is 600° C., and the calcination time is 3 hours.

[0018] Another object of the present invention is to provide a catalyst for catalyzing the conversion of glucose into 5-hydroxymethylfurfural, which is prepared by the preparation method described in the above embodiment.

[0019] Compared with the prior art, the beneficial technical effects of the present invention are: the mesoporous carbon microspheres loaded with tin prepared by the present invention have a large specific surface area, an excellent pore structure and good hydrothermal stability, and the mesoporous carbon microspheres loaded with tin have both Lewis acid and The two acidic sites of acid can efficiently catalyze the conversion of glucose into 5-hydroxymethylfurfural. In the field of biomass conversion, especially in the conversion of glucose into 5-hydroxymethylfurfural, it shows significant effects, providing a green and feasible way to achieve efficient conversion of glucose into 5-hydroxymethylfurfural. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The XRD spectra of xSnO2 / MCMs, MCMs prepared in each example, 20% SnO2 / AC prepared in Comparative Example 1, and AC.

[0021] Figure 2 It is the FTIR spectrum of 20% SnO2 / MCMs and MCMs prepared in Example 1.

[0022] Figure 3 are scanning electron microscope images of xSnO2 / MCMs and MCMs prepared in different embodiments, wherein a, b and c are SEM images of MCMs at different magnifications, d is the SEM image of 10% SnO2 / MCMs, e is the SEM image of 20% SnO2 / MCMs, and f is the SEM image of 30% SnO2 / MCMs.

[0023] Figure 4 are transmission electron microscope images of 20% SnO2 / MCMs prepared in Example 1, wherein a, b, c and d are TEM images of 20% SnO2 / MCMs, and e and f are EDX images of 20% SnO2 / MCMs.

[0024] Figure 5 It is a graph showing the nitrogen adsorption and desorption experimental results of xSnO2 / MCMs and MCMs prepared in different embodiments.

[0025] Figure 6 It is the pore size distribution diagram of xSnO2 / MCMs and MCMs prepared in different embodiments.

[0026] Figure 7 This is the pyridine infrared image of 20% SnO2 / MCMs and MCMs prepared in Example 1.

[0027] Figure 8 It is the TGA chart of xSnO2 / MCMs and MCMs prepared in each example.

[0028] Fig. 9 It is a comparison chart of the experimental results of xSnO2 / MCMs, MCMs prepared in each example, 20% SnO2 / AC prepared in Comparative Example 1, and AC catalyzing the conversion of glucose into HMF. DETAILED DESCRIPTION

[0029] The invention uses sucrose as a carbon source and tetraethyl silicate as a silicon source, synthesizes mesoporous carbon microspheres (MCMs) by a hard template method, and then uses an impregnation method to impregnate MCMs with a tin tetrachloride pentahydrate (SnCl4·5H2O) solution to prepare a xSnO2 / MCMs catalyst. The method comprises the following steps: (1) using hexadecyltrimethylammonium bromide (CTAB) as a structure directing agent, ammonia water to provide an alkaline environment, and tetraethyl orthosilicate (TEOS) as a silicon source of silicon dioxide to synthesize hollow mesoporous silicon spheres (HMSMs) in the presence of anhydrous ethanol; (2) using sucrose as a carbon source to fill the hollow mesoporous silicon spheres, and then carbonizing and removing silicon to obtain mesoporous carbon microspheres (MCMs); (3) impregnating MCMs with a SnCl4·5H2O solution to prepare a xSnO2 / MCMs catalyst.

[0030] The present invention is described in detail below through specific embodiments.

[0031] Raw material preparation: tetraethyl orthosilicate (TEOS, 98%, Macklin), hexadecyltrimethylammonium bromide (CTAB, 99%, Macklin), ammonium hydroxide solution (NH4OH, 25%-28%, Aladdin), anhydrous ethanol (C2H6O, 99.7%, Macklin), sucrose (99.7%, Sinopharm Chemical Reagent Co., Ltd.), sulfuric acid (H2SO4, 98%, Sinopharm Chemical Reagent Co., Ltd.), hydrofluoric acid (HF, 30%, Sinopharm Group Chemical Reagent Co., Ltd.), tin tetrachloride pentahydrate (SnCl4·5H2O, 99.995%, Macklin).

[0032] Example 1: Preparation of a catalyst for catalyzing the conversion of glucose into 5-hydroxymethylfurfural: (1) Hollow mesoporous silica spheres (HMSMs) were synthesized in the presence of anhydrous ethanol using CTAB as a structure directing agent, ammonia water as an alkaline environment, and TEOS as a silicon source for silica.

[0033] First, 0.9402 g CTAB, 34.8 mL of 25%-28% ammonia water, 130.14 mL of anhydrous ethanol and 288 mL of distilled water were added to a beaker in sequence and stirred at 40 °C for 1 h. After cooling to 25 °C, 5.373 g of TEOS was added and stirred vigorously. After standing at room temperature for 24 h, the mixture was filtered through a microporous filter membrane until it was neutral and dried. Then, it was calcined in a muffle furnace at 550 °C for 6 h to obtain hollow mesoporous silica spheres (HMSMs).

[0034] (2) Sucrose was used as the carbon source to fill hollow mesoporous silica spheres, and then mesoporous carbon microspheres (MCMs) were obtained through carbonization and silicon removal.

[0035] 1 g of hollow mesoporous silica spheres were dissolved in a sucrose aqueous solution containing sulfuric acid (1.25 g of sucrose, 0.1 mL of 98% concentrated sulfuric acid and 5 g of H2O were mixed), stirred, and then treated in an oven at 100°C and 160°C for 6 h, respectively, to obtain the initial filling sample.

[0036] In order to prevent inadequate filling, a secondary filling is required. The first filling sample is dissolved in a sucrose aqueous solution containing sulfuric acid (0.8 g sucrose, 0.05 mL 98% concentrated sulfuric acid and 5 g H2O mixed), stirred and treated in an oven at 100°C and 160°C for 6 hours respectively to obtain a secondary filling sample.

[0037] The secondary filling sample was calcined at 900° C. for 4 h in a tube furnace under a nitrogen atmosphere, and soaked in 40% hydrofluoric acid for 5 h. Finally, it was washed with deionized water until neutral, and mesoporous carbon microspheres (MCMs) were obtained after drying.

[0038] (3) 0.65638 g SnCl4·5H2O was dissolved in 30 mL deionized water, 1 g mesoporous carbon microspheres were added, stirred for 1 h, impregnated for 6 h, and then dried in an oven at 60°C. Finally, calcined at 600°C for 3 h in a tubular furnace under a nitrogen atmosphere to obtain a 20% SnO2 / MCMs catalyst.

[0039] Example 2: The difference from Example 1 is that in step (3), the amount of SnCl4·5H2O used is 0.32819 g, and a 10% SnO2 / MCMs catalyst is obtained.

[0040] Example 3: The difference from Example 1 is that in step (3), the amount of SnCl4·5H2O used is 0.98457 g, and 30% SnO2 / MCMs is obtained.

[0041] Comparative Example 1: 0.65638 g SnCl4·5H2O was dissolved in 30 mL deionized water, 1 g activated carbon (AC) was added, stirred for 1 h, impregnated for 6 h, and then dried in an oven at 60°C. Finally, the mixture was calcined at 600°C for 3 h in a tubular furnace under a nitrogen atmosphere to obtain tin-loaded activated carbon (20% SnO2 / AC).

[0042] In order to prove the metal oxides and functional groups contained in the xSnO2 / MCMs catalysts prepared in each example, the xSnO2 / MCMs catalysts and MCMs prepared in each example and the 20% SnO2 / AC and AC prepared in Comparative Example 1 were subjected to X-ray diffraction ( Figure 1 ), the 20% SnO2 / MCMs catalyst and MCMs prepared in Example 1 were tested by Fourier infrared spectroscopy ( Figure 2 ).Depend on Figure 1 and Figure 2As shown in Figure 2, the Sn loaded in the 20% SnO2 / MCMs catalyst is in the form of SnO2, and the dispersion of SnO2 loaded in the 20% SnO2 / MCMs catalyst is higher. Figure 2 It can be seen that MCMs contain acidic functional groups such as -OH and -COOH.

[0043] In order to explore the morphology and internal structure of the 20% SnO2 / MCMs catalyst prepared in Example 1, it was tested by scanning electron microscopy and transmission electron microscopy. The results are as follows: Figure 3 and Figure 4 As shown, the MCMs and 20% SnO2 / MCMs particles are evenly distributed and present a microspherical morphology, the SnO2 grains are evenly dispersed on the surface of the carbon microspheres, and the C, O and Sn elements are evenly distributed on the 20% SnO2 / MCMs catalyst.

[0044] In order to prove that the xSnO2 / MCMs catalyst prepared in each example has an excellent pore structure with a large specific surface area, the xSnO2 / MCMs catalyst prepared in each example and MCMs were subjected to nitrogen adsorption and desorption experiments. The results are as follows: Figure 5 The pore structures of the xSnO2 / MCMs catalysts and MCMs prepared in each example were determined by the BET method. The results are shown in Figure 6 Both MCMs and 20% SnO2 / MCMs present typical type IV curves, indicating that the pores are mainly mesoporous, and the curves contain clear H1 hysteresis loops, indicating that the porous characteristics of the carbon microspheres have cylindrical pore geometry and high pore size uniformity.

[0045] The specific surface area and pore structure of the xSnO2 / MCMs catalysts and MCMs prepared in each example and the AC and 20% SnO2 / AC in Comparative Example 1 were determined by the BET method. The results are shown in Table 1.

[0046] Table 1 Specific surface area and pore structure of different catalysts

[0047] catalyst <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Pore ​​size (nm) MCMs 865 0.68 4.5 <![CDATA[10%SnO2 / MCMs]]> 756 0.58 5.7 <![CDATA[20%SnO2 / MCMs]]> 753 0.55 4.8 <![CDATA[30%SnO2 / MCMs]]> 665 0.46 5.5 AC 32.3 0.021 2.7 <![CDATA[20%SnO2 / AC]]> 171 0.053 2.6

[0048] According to the results in Table 1, both MCMs and 20% SnO2 / MCMs have high specific surface areas and uniform large pore sizes.

[0049] In order to prove that the 20% SnO2 / MCMs catalyst prepared in Example 1 has both Lewis acid and The 20% SnO2 / MCMs catalyst prepared in Example 1 and MCMs were subjected to pyridine infrared testing. The results are as follows Figure 7The peak of Lewis acid in 20% SnO2 / MCMs is much stronger than that in MCMs, indicating that SnO2 loaded on the catalyst successfully plays the role of providing Lewis acid sites.

[0050] In order to prove that the xSnO2 / MCMs catalyst prepared in each example has good thermal stability, the xSnO2 / MCMs catalyst prepared in each example and MCMs were subjected to thermogravimetric tests. The results are as follows: Figure 8 As shown, the xSnO2 / MCMs catalyst prepared in each example has thermal stability and maintains its structure and performance at a temperature up to 450°C.

[0051] In order to demonstrate the excellent catalytic effect of tin-loaded mesoporous carbon microspheres xSnO2 / MCMs, the applicant compared the catalytic performance of mesoporous carbon microspheres, commercial activated carbon, 20% SnO2 / AC of tin-loaded activated carbon prepared in Comparative Example 1, and tin-loaded mesoporous carbon microspheres xSnO2 / MCMs prepared in various embodiments. The catalytic performance of various catalysts in catalyzing the conversion of glucose into HMF was compared under the same experimental conditions (temperature, time, solvent, etc.). The experimental results are as follows: Fig. 9 As shown, under the optimal experimental conditions (170℃, 5h), 20% SnO2 / MCMs exhibited excellent catalytic performance, the conversion rate of glucose in aqNaCl-H2O / THF biphasic solvent system was 94.9%, and the yield of HMF could reach 75.7%.

[0052] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A method for preparing a catalyst for catalyzing the conversion of glucose into 5-hydroxymethylfurfural, characterized in that: The following steps are involved: S1. Take hexadecyltrimethylammonium bromide, 25%-28% ammonia water, anhydrous ethanol and distilled water and add them to a beaker in sequence. After heating and stirring, cool to room temperature. Then add tetraethyl orthosilicate and stir vigorously. Let stand at room temperature for 24 hours, and calcine in a muffle furnace to synthesize hollow mesoporous silica spheres. S2, dissolving the hollow mesoporous silica spheres in a sucrose aqueous solution containing sulfuric acid, and baking them twice in an oven to obtain a primary filling sample; S3, dissolving the first filling sample in a sucrose aqueous solution containing sulfuric acid, and baking it twice in an oven to obtain a second filling sample; The secondary filling sample was calcined in a tubular furnace, then soaked in hydrofluoric acid, and finally washed with deionized water until neutral to obtain mesoporous carbon microspheres. S4. Take tin tetrachloride pentahydrate and dissolve it in deionized water, add mesoporous carbon microspheres and stir, after impregnation treatment, dry in an oven, and finally calcine in a tubular furnace to obtain xSnO2 / MCMs catalyst.

2. The method for preparing a catalyst for catalyzing the conversion of glucose into 5-hydroxymethylfurfural according to claim 1, characterized in that: In step S1, the mass ratio of hexadecyltrimethylammonium bromide to tetraethyl orthosilicate is 1:5.7, the volume ratio of ammonia water, anhydrous ethanol and distilled water is 1:3.74:8.28, and the dosage ratio of hexadecyltrimethylammonium bromide to ammonia water is 1 g:37 mL.

3. The method for preparing a catalyst for catalyzing the conversion of glucose into 5-hydroxymethylfurfural according to claim 2, characterized in that: In step S1, the heating and stirring temperature is 40° C., and the stirring time is 1 h.

4. The method for preparing a catalyst for catalyzing the conversion of glucose into 5-hydroxymethylfurfural according to claim 3, characterized in that: In step S1, the temperature of the muffle furnace calcination is 550° C., and the calcination time is 6 hours.

5. The method for preparing a catalyst for catalyzing the conversion of glucose into 5-hydroxymethylfurfural according to claim 4, characterized in that: The preparation method of the sucrose aqueous solution containing sulfuric acid in step S2 is: sucrose, 98% concentrated sulfuric acid and deionized water are uniformly mixed, and the usage ratio of the sucrose, concentrated sulfuric acid and deionized water is 12.5g:1mL:50g; The preparation method of the sucrose aqueous solution containing sulfuric acid in step S3 is: sucrose, 98% concentrated sulfuric acid and deionized water are mixed evenly, and the usage ratio of the sucrose, concentrated sulfuric acid and deionized water is 16g:1mL:100g.

6. The method for preparing a catalyst for catalyzing the conversion of glucose into 5-hydroxymethylfurfural according to claim 5, characterized in that: In step S2, the oven is baked twice at 100°C for 6 hours and at 160°C for 6 hours respectively; in step S3, the oven is baked twice at 100°C for 6 hours and at 160°C for 6 hours respectively.

7. The method for preparing a catalyst for catalyzing the conversion of glucose into 5-hydroxymethylfurfural according to claim 6, characterized in that: In step S3, the calcination treatment conditions in the tubular furnace are: calcination at 900° C. for 4 hours; in step S3, the mass percentage concentration of hydrofluoric acid is 40%, and the immersion time is 5 hours.

8. The method for preparing a catalyst for catalyzing the conversion of glucose into 5-hydroxymethylfurfural according to claim 7, characterized in that: In step S4, the stirring time is 1 hour, the impregnation time is 6 hours, the oven drying temperature is 60° C., the tubular furnace calcination temperature is 600° C., and the calcination time is 3 hours.

9. A catalyst for catalyzing the conversion of glucose into 5-hydroxymethylfurfural, characterized in that: The method is prepared according to any one of claims 1 to 8.

Citation Information

Cited By

  • Sn-Fe bimetal doped rice hull catalyst and preparation method and application thereof

    CN120502332A

  • Solid acid catalyst as well as preparation method and application thereof

    CN122343105A